Systems Engineering Principles and Practice, 2nd Edition - Steven M. Biemer; Alexander Kossiakoff; Samuel J. Seymour; William N. Sweet (Wiley-Interscience, 2011)
The Bestselling Guide to the Engineering of Complex Systems, Now Thoroughly UpdatedThe first edition of this unique interdisciplinary guide has become the foundational systems engineering textbook for colleges and universities worldwide. It has helped countless readers learn to think like systems engineers, giving them the knowledge, skills, and leadership qualities they need to be successful professionals. Now, colleagues of the original authors have upgraded and expanded the book to address the significant advances in this rapidly changing field.An outgrowth of the Johns Hopkins University Master of Science Program in Engineering, Systems Engineering: Principles and Practice provides an educationally sound, entry-level approach to the subject, describing tools and techniques essential for the development of complex systems. Exhaustively classroom tested, the text continues the tradition of utilizing models to assist in grasping abstract concepts, emphasizing application and practice. This Second Edition features:Expanded topics on advanced systems engineering concepts beyond the traditional systems engineering areas and the post-development stageUpdated DOD and commercial standards, architectures, and processesNew models and frameworks for traditional structured analysis and object-oriented analysis techniquesImproved discussions on requirements, systems management, functional analysis, analysis of alternatives, decision making and support, and operational analysisSupplemental material on the concept of the system boundaryModern software engineering techniques, principles, and conceptsFurther exploration of the system engineer's career to guide prospective professionalsUpdated problems and referencesThe Second Edition continues to serve as a graduate-level textbook for courses introducing the field and practice of systems engineering. This very readable book is also an excellent resource for engineers, scientists, and project managers involved with systems engineering, as well as a useful textbook for short courses offered through industry seminars.